Risk Factors for Psychological Impact and Stigma Among Leprosy Patients: A Systematic Review - Rasyidi, Nuri Firdausyiah; Yusuf, Ah; Tristiana, Rr Dian (GLOBAL HEALTH SCIENCE GROUP, 2024)
The bacterium Mycobacterium leprae causes leprosy, which causes peripheral neuropathy and prolonged disability that impacts a person's psychology, causing fear and anxiety. The aim of this review study was to find variables that impact on individuals' mental health and social stigma. Method: A systematic review searched for previous studies using cross-sectional or non-experimental designs published between 2019 and 2024 in five electronic databases (Scopus, Wos, Science Direct, and ProQuest). To transfer this view, the Center for Research and Dissemination and the Joanna Briggs Institute Guidelines were used to assess quality and the Prisma checklist. To assess research eligibility, titles, abstracts, full texts, and methodologies were evaluated. Data tabulation and narrative analysis of research results were conducted. Results: We found that seven journals met the requirements for inclusion in this observation. Any research on psychology and stigma addresses psychological impact and factors related to social stigma. Psychological impacts include knowledge, gender, culture, disability, economy, education, and lack of support systems, while stigma includes societal culture and the disability of leprosy. Conclusion: The results of this systematic review found many things that are risk factors for psychological disorders and stigma in leprosy patients including knowledge, gender, culture economy, education and lack of support system, disability which causes leprosy sufferers to experience discrimination, self-isolation, and misperceptions from society. Further research to understand this phenomenon is needed to reduce the global psychological impact and negative social stigma.